Prevalence and psychological correlates of binge-watching: The digital era of entertainment - Maumita Sil; Anwesha Mondal; Manish Kumar (Industrial Psychiatry Journal)
Background: Binge-watching refers to watching multiple television series episodes in one sitting. The concept of narratives and the immersive nature of the storyline are highlighted in the binge-watching phenomenon. Binge-watching has been compared with the addiction model, which impacts both mental and physical health. Different studies in the West have come up with different binge-watch profiles, but in India, the literature on binge-watching is scarce. Aim: The present study aims to explore the prevalence of binge-watching behavior and determine the relationship between binge-watching and the psychological correlates, namely, stress, depression, anxiety, coping styles, and personality traits. Materials and Methods: The current study was conducted online on a community sample consisting of 235 individuals. Binge-watching behavior was assessed through the Binge-Watching Engagement and Symptoms Questionnaire (BWESQ), and psychological correlates were assessed through DASS 21, Brief COPE, and Big Five Invenrory-2-Short (BFI-2-S). Results: A high prevalence rate (85%) for binge-watching has been found. Avoidance coping style increases binge-watching behavior. Conscientiousness personality trait decreases binge-watching, and extraversion increases it. Conclusion: Binge-watching is a prevalent phenomenon in the community and coping styles, and personality traits can influence binge-watching behavior in a bidirectional manner.